Anxiety Of Mothers Who Have Toddlers During The Covid-19 Pandemic - Khaqiqi, Kharishma; Chabibah, Nur; Khuzaiyah, Siti (Prosiding University Research Colloquium, 2022)
The threat of COVID-19 is not only for adults but also for children. The COVID-19 pandemic has a psychological effect, a heavy stressor for mothers who have children. The purpose of this study was to look at the anxiety of mothers who have toddlers during the COVID-19 pandemic and the factors that influence it. The method used is descriptive quantitative exploring the anxiety of mothers who have health toddlers. The sample size in this study was 107 mothers who had children from 0 months to 5 years of age. This anxiety questionnaire was prepared by modifying the HARS (Hamilton Anxiety Rating Scale). Data collection was carried out by distributing google forms via WhatsApp groups to eight-village toddler classes in the Pekalongan Regency area. The results showed that mothers who had toddlers felt very heavy anxiety (51.4%) due to the covid-19 pandemic. This level of anxiety is related to the mother's working status (-0.0153) and the age of the youngest child (0.0326). This study concludes that the anxiety of mothers who have toddlers is very high due to the covid-19 pandemic. The level of anxiety is influenced by the status of working mothers and the age of the youngest child. The smaller the age of the child, the higher the mother's anxiety about the health of the toddler. Therefore, the role of health workers in providing accurate and fast information during a pandemic is very significant in reducing the level of anxiety for mothers who have toddlers. The role of health workers in providing accurate and fast information during a pandemic is very significant in reducing the level of anxiety for mothers who have toddlers.